Biospeleological researches. VI. Boldoria (Pseudoboldoria) belluccii new cavernicolous species of Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The Author describes Boldoria (Pseudobaldoria) belluccii n. sp. collected in three caves of the side of the Lake Iseo belonging to the Bergamo district. This new species is related to Boldoria (Pseudoboldoria) gratiae Monguzzi, from which can be distinguished due to the particular characters of aedeagus and for other exoskeleton characteristics.